Conservation Status and Medicinal Plants of the Family Euphorbiaceae in Tirunelveli Hills, Southern India - S. Ignacimuthu2, M. Ayyanar1* and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Tirunelveli hills of Tamil Nadu harbour over 2000 species of plants, of which 25% are endemic and 3% are under various categories of threat. An ethnobotanical survey was carried out among the tribal people (kani/kanikaran) inhabiting the Tirunelveli hills of Tamil Nadu and the study revealed that, they are using more than 350 plants to prepare medicine, of which 8% (30 species) are belongs to the family Euphorbiaceae and it is consistent with the claim by the floristic diversity of this family. In floristic survey, Euphorbiaceae is one of the best-represented families in Tirunelveli hills of Tamil Nadu with 124 species of plants belonging to 34 genera and ranks third followed by Leguminosae and Poaceae in terms of number of species. The largest genera in Euphorbiaceae are Phyllanthus, Euphorbia and Mallotus, each with 21, 18 and 11 species respectively. Euphorbiaceae includes more number of endemic plants with 31 sps. and the genus Phyllanthus includes five endemic species; Blachia, Drypetes, Euphorbia, Glochidion and Mallotus with three species. The plants such as Blachia calycina Benth., Blachia umbellata Baill., Dimorphocalyx lawianus (M.Arg.) Hk.f., Mallotus stenanthus M.Arg., Phyllanthus baillonianus M.Arg. and Baccaurea courtallensis M.Arg. are identified as endemic medicinal plants. Majority of the plants present in these hills are rapidly threatened by anthropogenic activities due to several pilgrim and tourist places within the forest area. Its biodiversity is vulnerable due to different factors, and its conservation should be paid enormous attention by involving the local communities and forest representatives in preservation and conservation aspects. Key words: Tirunelveli hills, Endemism, Euphorbiaceae, Medicinal plants, Threat status --- 1Division of Biodiversity and Biotechnology, Department of Botany, Pachaiyappa’s College, Chennai - 600030, Tamil Nadu, India; 2Entomology Research Institute, Loyola college, Chennai – 600 034; Tamil Nadu, India --- Please Cite This Article As: M. Ayyanar and S. Ignacimuthu. 2010. Diversity, Conservation Status and Medicinal Plants of the Family Euphorbiaceae in Tirunelveli Hills, Southern India. J. Exp. Sci. 1(6):12-16.